Healthy Eating Index Protocol: Review, Update, and Development Process to Reflect Dietary Guidance Across the Lifespan. (7th June 2021) - Reedy, Jill; Pannucci, TusaRebecca; Herrick, Kirsten; Lerman, Jennifer; Shams-White, Marissa; Zimmer, Meghan
Abstract: Objectives: The Healthy Eating Index (HEI) is a measure of diet quality, independent of quantity, that can be used to assess alignment with the Dietary Guidelines for Americans (DGAs), which are the basis of nutrition policy for the United States (US) government and the foundation of all federal nutrition guidance. The recently released 2020–2025 DGAs include recommendations for infants and toddlers for the first time, and necessitate a review, update, and development process of the HEI to reflect healthy eating across the lifespan. Methods: Since 2005, researchers at the HHS National Cancer Institute (NCI) and the USDA Center for Nutrition Policy and Promotion have collaborated to revise the HEI based on updates to the DGAs, and the HEI-2015 is the most recent iteration. The process includes: 1 ) gathering information from dietary guidelines, experts, and federal stakeholders; 2 ) considering substantive changes and needs for new development; and 3 ) completing validation analyses. Results: Updates to the HEI have aimed to maintain stability, reflecting the consistency of recommendations over time. A guiding principle is to only make changes to the HEI that have a strong rationale. With no significant changes in the USDA Dietary Patterns, few changes are anticipated for the HEI for 2 years and older; instead, the emphasis for the update process is focusing on considerations for an index for infants and toddlers under 2 years. Additionally, the Scientific Report of the 2020 Dietary Guidelines Advisory Committee identified the development of a scoring system (such as the HEI) for infants and toddlers as a research recommendation, because comparisons of diet quality using the HEI have thus far only been possible for Americans 2 years and older. The HEI review, update, and development process aims to consider analyses with distributions of HEI scores across the lifespan with nationally representative data and diverse cohorts. Conclusions: The HEI is a valuable tool for research that can be used in nutrition interventions, epidemiology, and consumer nutrition education programs. The timely release of a new HEI will enable application across the lifespan and support additional methodological research to examine needs specific to each life stage and how to model optimal trajectories of healthy dietary patterns. Funding Sources: None.